(untitled) (Studia Prawnicze / The Legal Studies, 2024)
Artykuł dotyczy doświadczeń z okresu „dużego” rozszerzenia UE, które objęło również Polskę, odnoszących się do włączenia ówczesnych 12 państw kandydujących do systemu instytucjonalnego WE/UE. Ograniczono przy tym zakres analizy do tych doświadczeniach, które zachowały aktualność i mogą mieć znaczenie obecnie dla negocjacji akcesyjnych z grupą państw aspirujących do członkostwa. Do takich doświadczeń zaliczono: regułę aktywnej partycypacji w debacie nad reformami instytucjonalnymi UE, regułę „demograficzną”, regułę egalitarnej rotacji, regułę uprzywilejowania nowego państwa członkowskiego, regułę elastyczności i zachowania równowagi między małymi, średnimi i dużymi państwami członkowskimi oraz regułę praworządności, czyli wymóg ścisłego spełnienia pierwszego kryterium kopenhaskiego. [The article concerns the experiences of the period of “large” enlargement of the EU, which also included Poland, referring to the inclusion of the then 12 candidate countries into the EC/EU institutional system. At the same time, the scope of the analysis has been limited to those experiences that have remained relevant and may now be interesting for accession negotiations with a group of countries aspiring to membership. Such experiences include: the principle of active participation in the debate on the EU’s institutional reforms, the “demographic” rule, the principle of egalitarian rotation, the principle of favouring the new Member State, the principle of flexibility and maintaining balance between small, medium-sized and large Member States, and the rule of law, i.e. the requirement of strict compliance with the first Copenhagen criterion.]